Behavioural Study on Self Curing Concrete Using Poly Ethylene Glycol and Silica Fume - T. Senthil Vadivel, Dr.; Giri Prasad Goud, E.; Nagarjuna, S.; Doddurani, M.; P. Geethu, A. (International Journal of Engineering and Technology, 2018)
Water has a major role throughout the life of the concrete, because it is a critical component in the mixing, curing and hardening. Water obtained by the curing of concrete maintains satisfactory moisture content in order to achieve the desired properties developing the concrete microstructure and pore structure and hence improves its durability and performance. But, good curing is not always practical in many cases. So attempts have been made to develop internal curing concrete in which internal â€“ curing agent provides water internally which is distributed throughout the concrete matrix whereas plain concrete is completely dependent on surface curing which only penetrates concrete surface by a few millimeter. Keeping importance to this, an attempt has been made to develop internal-curing concrete by using Poly Ethylene Glycol (PEG-400). In this experimental analysis the strength characteristics of conventional concrete and self curing concrete, cast with the self-curing agent PEG-400 have been studied and compared. M30 grade of concrete is adopted using IS method of mix design. For the production of internal-curing concrete trial fractions of 1%, 2% and 3% of PEG-400 and silica fume of 15%, 18% and 20% by weight of cement was used and tested for different mechanical properties and found that 1% PEG at 20% silica fume is the optimal among all mixes.Â Â